TO THE EDITOR - Geller, Stephen A. (Autopsy and Case Reports, 2013)
The current issue of Autopsy and Case Reports (2013;3(1):5-14) has an interesting report by Cavalcante et al. purporting to describe an additional case of “hepatoid carcinoma.” Unfortunately, the case description does not fully satisfy the criteria for that diagnosis.